Blind killing of both male and female Drosophila embryos by a natural variant of the endosymbiotic bacterium Spiroplasma poulsonii. (23rd January 2020) - Masson, Florent; Calderon‐Copete, Sandra; Schüpfer, Fanny; Vigneron, Aurélien; Rommelaere, Samuel; Garcia‐Arraez, Mario G.; Paredes, Juan C.; Lemaitre, Bruno
Abstract: Spiroplasma poulsonii is a vertically transmitted endosymbiont of Drosophila melanogaster that causes male‐killing, that is the death of infected male embryos during embryogenesis. Here, we report a natural variant of S. poulsonii that is efficiently vertically transmitted yet does not selectively kill males, but kills rather a subset of all embryos regardless of their sex, a phenotype we call 'blind‐killing'. We show that the natural plasmid of S. poulsonii has an altered structure: Spaid, the gene coding for the male‐killing toxin, is deleted in the blind‐killing strain, confirming its function as a male‐killing factor. Then we further investigate several hypotheses that could explain the sex‐independent toxicity of this new strain on host embryos. As the second non‐male‐killing variant isolated from a male‐killing original population, this new strain raises questions on how male‐killing is maintained or lost in fly populations. As a natural knock‐out of Spaid, which is unachievable yet by genetic engineering approaches, this variant also represents a valuable tool for further investigations on the male‐killing mechanism.